Transient response of magnetorheological fluid on rapid change of magnetic field in shear mode - Michal Kubík; Josef Válek; Jiří Žáček; Filip Jeniš; Dmitry Borin; Zbyněk Strecker; Ivan Mazůrek (Scientific Reports, 2022)
Abstract The transient behaviour of magnetorheological (MR) devices is an important parameter for modern semi-actively controlled suspension systems. A significant part of the MR device response time is the MR fluid response time itself. A significant factor is the so-called rheological response time. The rheological response time is connected with the structuring particle's time and the development of shear stress in MR fluid during the deformation. The main aim of this paper is to experimentally determine the rheological response time of MR fluid and evaluated the effect of shear rate, magnetic field level, and carrier fluid viscosity. The unique design of the rheometer, which allows the rapid change of a magnetic field, is presented. The rheological response time of MRF 132-DG and MRC-C1L is in the range of 0.8–1.4 ms, depending on the shear rate. The higher the shear rate, the shorter the response time. It can be stated that the higher the magnetization of the MR fluid, the lower the response time. The higher the viscosity, the higher the rheological response time. The measured data of rheological response time was generalized and one master curve was determined.